The effect of counseling on adolescent knowledge about the impact of free sex at SMA Negeri 6 Palu: Pengaruh penyuluhan terhadap pengetahuan remaja tentang dampak seks bebas di SMA Negeri 6 Palu - Yuli Vebrianti; Sumiaty Sumiaty; Sri Yanti Kusika; Siti Hadijah Batjo (Poltekkes Kemenkes Palu, 2022)
Background: The impact of free sex on adolescents is physical danger, such as being exposed to venereal diseases (sexually transmitted diseases/STDs) and HIV/AIDS as well as the dangers of unwanted early pregnancy. In 2020, Central Sulawesi Province reported as many as 367 cases of HIV Positive, Unwanted Pregnancy (KTD) in adolescents as many as 24 people. Objective: to determine the effect of counseling on adolescent knowledge about the impact of free sex at Middle School 6 Palu. Methods: Pre-experiment with one group pretest-posttest design. using the Lemeshow formula. The population of all class x students at SMAN 6 Palu is 185 people, and the sample is 126 by proportional random sampling. The analysis consisted of univariate and bivariate with Wilcoxon test. Results: Before being given counseling, it showed that there was a lack of knowledge of adolescents about the impact of free sex, but after being given counseling, adolescent knowledge increased, with a p-value of 0.000 p-value <0.05, meaning that there was an effect of counseling on the impact of free sex in SMA Negeri 6 Hammers. Conclusion: Counseling can increase adolescent knowledge about the impact of free sex in SMA Negeri 6 Palu. Suggestions can be carried out periodically to prevent free sex behavior in adolescents.